The Impact of Relocating Illegal Settlement at Simpang Barelang, Batam City, Riau Islands - Murtiono, Hendro (Universitas Ibn Khaldun Bogor, 2023)
Slum settlements in Batam City are mostly inhabited by poor people who are unable to access proper housing. The inability of the poor to access these decent settlements, makes them choose to live in slum settlements with inadequate basic facilities and infrastructure. Relocation or resettlement is an alternative to provide opportunities for people living in slum settlements, whose land status is illegal or living in a disaster-prone environment to reorganize and continue their lives in a new place. This research was structured with the aim of knowing how the implementation of the relocation program for occupation settlements at the Simpang Barelang in the city of Batam. As a qualitative and quantitative descriptive research, the results of this study have both positive and negative impacts. In terms of physical conditions, relocation provides positive changes to the current settlement conditions. Then the social impact of the relocation carried out in the Tembesi Village, has also been successful in maintaining the social order that has been formed. However, in terms of the community's economy, the relocation program had a negative impact due to the loss of sources of income and decreased community income.